Longer-term effects of monetary growth on real and nominal variables, major industrial countries, 1880-2001 - Alfred A. Haug; William G. Dewald (European Central Bank (ECB), 2004)
Abstract: We study how fluctuations in money growth correlate with fluctuations in real and nominal output growth and inflation. We pick cycles from each time series that last 2 to 8 (business cycles) and 8 to 40 (longer-term cycles) years, using band-pass filters. We employ a data set from 1880 to 2001 for eleven countries, without gaps. Fluctuations in money growth do not play a systematic and important role at the business cycle frequency. However, money growth leads or contemporaneously affects nominal output growth and inflation in the longer run. This result holds despite differences in policies and institutions across countries.
Keywords: E3; 330; 2 to 8 year cycles; 8 to 40 year cycles; Band-pass filters